Global trends of antimicrobial resistance rates in Neisseria gonorrhoeae: a systematic review and meta-analysis - Hooshiar, Mohammad Hosseini; Sholeh, Mohammad; Beig, Masoumeh; Azizian, Khalil; Kouhsari, Ebrahim (Frontiers in Pharmacology, 2024)
Background: Antimicrobial resistance (AMR) of Neisseria gonorrhoeae (NG) is a significant public health concern. Objective: The objective of our study was to assess global AMR rates and testing both temporally and geographically. Methods: We conducted a systematic search of relevant reports from international databases up to 2021. The R statistical package was used for all statistical analyses. Results: A total of 225 articles were analyzed, and 432,880 NG isolates were examined. The weighted pooled resistance rate (WPR) of different antibiotics were as follows: ciprofloxacin, 51.6%; tetracycline, 45.4%; trimethoprim/sulfamethoxazole, 42.4%; chloramphenicol, 4.1%; kanamycin, 2.1%; gentamicin, 0.6%; and spectinomycin, 0.3%. The resistance to spectinomycin, gentamicin, and kanamycin decreased over time. Significant differences in antibiotic resistance rates were found between the countries. Conclusion: Our findings reveal a continuous increase in resistance to some antibiotics (tetracycline and ciprofloxacin) historically used for gonorrhea, even after discontinuation. However, encouraging trends of decreasing resistance to spectinomycin, gentamicin, and kanamycin were observed.Continued global monitoring of AMR profiles in NG isolates is essential for informing appropriate treatment strategies and mitigating the threat of untreatable gonorrhea.